Finding a Bravais lattice with higher symmetry from lattice parameters of a supercell - Yoyo Hinuma; Hiroyuki Ozaki (Science and Technology of Advanced Materials: Methods)
We present an advanced algorithm that systematically identifies Bravais lattices from diffraction data, such as powder X-ray, as these data are crucial for new material development. The algorithm efficiently generates an ‘augmented lattice’ with more lattice points than the original lattice. An ‘acceptable cell’ is defined for each Bravais lattice, quantifying the tolerance needed for accurate structural description despite experimental uncertainties. The algorithm was tested on lithium battery cathode materials and halide organometallic perovskites and demonstrated significant potential in enhancing material analysis and development through precise structural identification. This concise approach offers a robust framework for material scientists, facilitating rapid advancements in the field.